2018
DOI: 10.5539/ijef.v10n2p20
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Financial Statements and Its Effect on Investor’s Decision Making in Jordanian Commercial Banks

Abstract: This study aims to examine the effect of financial information on investors decision making in commercial banks in Jordan. A questionnaire was adopted to address attitudes of professionals such as managers, analysts and investors and to identify to which degree the financial information was used in taking investment decisions. The results revealed a weak positive relationship between investment decisions and financial information that were provided by commercial banks in Jordan to the investors. This study rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore, financial reports must be meticulously crafted and contain extensive transparency, embracing both financial and non-financial information within and beyond the financial statements. Hence, the main objective of financial reports is to furnish dependable information regarding the genuine and current financial status of a business venture, thereby aiding investors in formulating their investment choices (Saleh, Alghusain, 2018: 21) [21] . The Institute of Chartered Accountants in England and Wales (ICAEW) contends that even if corporations offer more general risk information rather than specific companyrelated information, there are two conflicting assumptions.…”
Section: Concept Of Investor Decisions and The Importance Of Accounti...mentioning
confidence: 99%
“…Furthermore, financial reports must be meticulously crafted and contain extensive transparency, embracing both financial and non-financial information within and beyond the financial statements. Hence, the main objective of financial reports is to furnish dependable information regarding the genuine and current financial status of a business venture, thereby aiding investors in formulating their investment choices (Saleh, Alghusain, 2018: 21) [21] . The Institute of Chartered Accountants in England and Wales (ICAEW) contends that even if corporations offer more general risk information rather than specific companyrelated information, there are two conflicting assumptions.…”
Section: Concept Of Investor Decisions and The Importance Of Accounti...mentioning
confidence: 99%
“…Information disclosed through several components of the annual report not only helps in making prompt investment decisions but also helps users make financing decisions. Isam & Nawaf (2018) analyzed the effect of disclosures of financial statements in investment decisions and found that trustworthy information can be found from annual financial statements, and Investors use the information provided through annual financial statements in making their investment decisions. An empirical study carried out by Kitindi, Magembe & Sethibe (2007) on lending decisions and found that statements contained in the annual reports were the key sources of information and helps lenders significantly in making their lending decision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most investors focus on the financial benefits of their investments [1]. Several studies have conducted investigations related to the influence of financial information on investment decisions [2][3][4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%